Peningkatan Soft Skill Siswa SMK PGRI Kediri Melalui Pelatihan Zahir Accounting - Erna Puspita; Puji Astuti; Andy Kurniawan; Hestin Sri Widiawati; Linawati Linawati; Diah Nurdiwaty (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2021)
This activity aims to increase the knowledge and soft skills of SMK students regarding accounting software. Students are given knowledge, understanding, and training to update accounting software from the software MYOB to Zahir Accounting, which is more developed following changes in accounting science and the needs of the modern business world. The activity was carried out at SMK PGRI 3 Kediri City. The participants of the exercise were students of SMK class XII. Implementation of activities in the form of training. The method of implementing the conditioning is done through lectures, practicum, and question and answer. The action is divided into two sessions. In the first session, the material explained Zahir Accounting software. In the second session, the Zahir Accounting software practicum was held, where participants could practice the accounting cycle directly using Zahir Accounting software. The participants participated in the training activities in a conducive and enthusiastic manner. The participants had no difficulty in implementing the training